2018
DOI: 10.1002/jcph.1332
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Therapy Use Increases the Risk of Heart Failure in Patients With Prostate Cancer: A Population‐Based Cohort Study

Abstract: The aim of this study was to investigate the relationship between androgen deprivation therapy and heart failure among prostate cancer patients. This cohort study used the data from the Taiwan Longitudinal Health Insurance Database 2005. In the full cohort study, we identified 1244 prostate cancer patients who had received androgen deprivation therapy as the study cohort and 1806 prostate cancer patients who did not receive androgen deprivation therapy as the comparison cohort. To eliminate potential bias, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…The main mediators of these effects are p53, heat shock protein HSP27, quinone reductases as well as nitric oxide [102]. Considering that several cancer therapies like androgen deprivation therapy are conceived to indirectly contribute to the development of hyperglycemia, dyslipidemia and metabolic syndrome, which are well-established causal risk factors of atherosclerosis [103,104], the use of resveratrol in this category of patients could be a therapeutic window of interest in the cardio-oncological field.…”
Section: Resveratrol In Cardio-oncologymentioning
confidence: 99%
“…The main mediators of these effects are p53, heat shock protein HSP27, quinone reductases as well as nitric oxide [102]. Considering that several cancer therapies like androgen deprivation therapy are conceived to indirectly contribute to the development of hyperglycemia, dyslipidemia and metabolic syndrome, which are well-established causal risk factors of atherosclerosis [103,104], the use of resveratrol in this category of patients could be a therapeutic window of interest in the cardio-oncological field.…”
Section: Resveratrol In Cardio-oncologymentioning
confidence: 99%
“…Emerging reports have indicated the wide-ranging impact of PCa treatment strategies like ADT on patients’ risk of developing CVDs, like hypertension, CAD, arrhythmia and cardiac arrests [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Though the interconnection between cardiovascular health and PCa has been reported, the molecular mechanisms underlying this interconnection have not been completely explored.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT) remains the cornerstone of treatment for metastatic PCa [ 4 , 5 , 6 , 7 ], but most patients experience disease relapse due to therapeutic failure. Several studies in recent times have suggested a strong connection between cardiovascular diseases (CVDs) and PCa [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. ADT reportedly elevates the risk for heart failure and other CVDs like hypertension and stroke in men without pre-existing cardiovascular conditions, which is even more in patients with pre-existing CVDs [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successively, fine results have been reported in NHIRD-related literature relating to breast cancer [17, 18] and hepatoma [19]. Prostate cancer–related issues with NHIRD have also been published [20, 21, 22]. However, these studies related to prostate cancer have not focused on cancerous recurrence or death.…”
Section: Introductionmentioning
confidence: 99%